Multiple sclerosis in the tropics: genetic association to STR's loci spanning the HLA and TNF (2002)
Clear evidence has been presented correlating gene polymorphisms at 6p21.3-21.4 (containing HLA and TNF) and the predisposition to acquire multiple sclerosis (MS). In a previous study, we found that polymorphisms at HLA DQA1 were associated with being or not being predisposed to MS in individuals inhabiting the tropics, where the prevalence of MS is significantly lower than in subtropical areas. Here, we tested the hypothesis that polymorphisms at D6S276, D6S265, D6S273 and D6S291 microsatellite loci are in strong linkage disequilibrium with a major genetic factor predisposing to MS. These microsatellites span the 6p21.3 region with intervals of 5 cM establishing particular landmarks for the HLA and TNF loci. Thirty-five MS patients and 35 controls, age, sex, social, ethnically and geographically matched healthy individuals, were studied. After testing the fit of gene frequencies to the normal distribution and performing the correlation for multiple comparisons, we found significant differences among the case and the control frequencies for the allele 202 belonging to the marker D6S276 (Pc =0.00455) and for the allele 114 belonging to the marker D6S265 (Pc=0.0084). For these two alleles at different loci, we found higher frequencies in the cases than in the controls. A nonsignificant p value was found in testing the existence of linkage disequilibrium among the studied loci in the cases and in the controls. In conclusion, the current study adds evidence to the established association among polymorphisms of genes located at 6p21.3-21.4 and MS. Furthermore, because of the distribution of the tested microsatellite loci, the more probable critical region could be correlated with the TNF neighborhood.